MOTOR CONVENTIONAL INSURANCE; ITS PREFERENCE AMONG MUSLIMS IN PETALING JAYA - Muhammad Amsyar Arshad; Ruhaizah Abdul Ghani (Journal of Islamic, Social, Economics and Development, 2022)
Motor insurance, whether convetional or Islamic one, is a part and parcel of buying vehicles as to cover certain cost for the damage that might occurs in any incidents as well as the cost for the treatment of certain injuries. This study will explore the Muslims preference on conventional insurance as well as further investigate the determinant factors of Muslims’ preference. As an explorative study, the research used qualitative method by interviewing respondents among Muslims in Petaling Jaya as to get the data. As a result, the data demonstrated that the determinant factors are lack of awareness on takaful and inefficient roles of agent in promoting the product. Thus, the researcher suggests that Takaful agencies to put extra effort in advertising, marketing and merging with vehicle companies.